Pembelajaran Multiliterasi: Implementasinya dalam Pelatihan Pengembangan Model Pembelajaran Guru SMA di Malang: Multiliteracy Learning: Its Implementation in Training for Development of Learning Models for High School Teachers in Malang - Arti Prihatini; Sugiarti Sugiarti (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
There was a limited teacher empowerment program to develop a multiliteracy-based learning model. The urgency of the program is quite substantial because learning barriers during the Covid19 pandemic must be overcome through innovative learning models that stimulate students' multiliteracy skills. This activity aims to empower high school teachers in developing a multiliteracy-based learning model to implement independent learning. This program consists of six meetings, including preparation, incubation, illumination, and verification stages. This activity was conducted online and offline for three months with 15 teachers from SMA Aisyiyah Boarding School Malang. The instruments used are worksheets and interview guides. It was declared successful if 75% of the participants got a minimum of 75 on the worksheet. The results showed that 87% of teachers had exceeded the minimum score. Most teachers have carried out the activities well, starting from the preparation, incubation, illumination, and verification stages. Teachers can find ideas, analyze learning needs, design and display learning models. Multiliteracy learning is implemented through various learning resources and critical literacy stimulation. The teachers' learning model has been applied to online and offline learning practices.